The influence of orientations and building designs on thermal performance in traditional houses, in Gayo highland region, Aceh, Indonesia / Salsabilla ... [et al.] - Salsabilla, -; Sari, Laina Hilma; Elysa, Wulandari; Agustina, Sylvia; Sabila, Farisa; Djamaluddin, Masdar; Taqiuddin, Zulfikar; Arafat, Pratitou (Universiti Teknologi MARA, Perak, 2023)
Gayonese traditional houses are called Umah Pitu Ruang (UPR) designed to adapt to the climatic conditions of the Gayo highland region in Indonesia. Gayo highland is well known for the cool humid climate zone in Aceh Province which is different from the lowland of Aceh i.e. hot humid. As a residential function, this building requires an adequate level of thermal comfort so that users can carry out their activities properly. This study aims to evaluate whether the thermal comfort performance in Umah Pitu Ruang (UPR) meets the standard; and to identify the influence of house orientation and building design in the thermal indoor environment. The research method used is a quantitative method obtained from the results of field observations and the results of measuring thermal comfort variables in the form of air temperature (Ta), relative humidity (Rh) and wind speed (v) in both Umah Pitu Ruang. Later the measurement results will be compared with Indonesian thermal comfort standard namely 03-6572-2001. The results showed that the thermal performance such as air temperature, relative humidity, and wind speed in Gayonese traditional houses did not meet the SNI standard. . The study also indicates that the orientation of the buildings is influential on thermal performance. Openings orienting west and east work more effectively in warming the interiors while at the same time the airflow running across the rooms. In contrast, orienting the openings to the north and the south is able to get slightly lower air temperature which is essential to be reduced during the day to be comfortable.